Dosimetry Check™를 이용한 MVCT 선량계산 모델 구축에 관한 연구 - 엄기천(Ki-Cheon Um), 김창환(Chang-Hwan Kim), 전수동(Soo-Dong Jeon), 백금문(Geum-Mun Back) (방사선기술과학, 2020)
The purpose of this study was to construct a model of MVCT(Megavoltage Computed Tomography) dose calculation by using Dosimetry Check™, a program that radiation treatment dose verification, and establish a protocol that can be accumulated to the radiation treatment dose distribution. We acquired sinogram of MVCT after air scan in Fine, Normal, Coarse mode. Dosimetry Check™(DC) program can analyze only DICOM(Digital Imaging Communications in Medicine) format, however acquired sinogram is dat format. Thus, we made MVCT RC-DICOM format by using acquired sinogram. In addition, we made MVCT RP-DICOM by using principle of generating MLC(Multi-leaf Collimator) control points at half location of pitch in treatment RP-DICOM. The MVCT imaging dose in fine mode was measured by using ionization chamber, and normalized to the MVCT dose calculation model, the MVCT imaging dose of Normal, Coarse mode was calculated by using DC program. As a results, 2.08 cGy was measured by using ionization chamber in Fine mode and normalized based on the measured dose in DC program. After normalization, the result of MVCT dose calculation in Normal, Coarse mode, each mode was calculated 0.957, 0.621 cGy. Finally, the dose resulting from the process for acquisition of MVCT can be accumulated to the treatment dose distribution for dose evaluation. It is believed that this could be contribute clinically to a more realistic dose evaluation. From now on, it is considered that it will be able to provide more accurate and realistic dose information in radiation therapy planning evaluation by using Tomotherapy.